Case studies about biomass district heating efficiency in Romania - Bitir-Istrate, Ioan (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Biomass became the perfect choice for heating in Romanian cities while the geopolitical situation remains still complicated. A selection of cases is presented with several cities using this fuel for heating. A cogeneration with steam boilers, new boilers for warm water or obsoleted ones are all investigated from technical and economical perspectives. The article includes correlations with number of inhabitants, buildings connected to the grid, economical aspects. Conclusions are obtained about the efficiency of biomass district heating for different sizes cities, for different technologies and opportunity to implement modernization projects. The results can enhance the local efforts for a better use of biomass in municipal heating without greenhouse gas emissions. Statistical data about Romanian district heating performance indicators have been used and approved tariffs against average revenues of the population were considered.